KCPR Archives 1976 (1976)
Fall 76 [00:00:12] Sign On (Jaz) [00:01:09] Sign Off (Jaz) [00:02:08] Cont. B ID (Jaz) [00:03:08] License Renewal (DDR) [00:04:05] KCPR Open Jingles Spots [00:04:57] Sunday By Request (M.E. and Aaron Baker) [00:05:52] Lone Star Promo 6-Midnight (D.H.) [00:06:38] Morning Man #1 [00:07:52] Morning Man #2 [00:09:13] Morning Man #3 - mystery microphone at UU [00:10:29] Auction Promo Sunday, Nov 14 (ME and DRR) [00:12:02] Morning Man #4 (Jaz, 11/16/76) - mystery microphone at snack bar [00:12:54] Marv Miller Promo (R.K) [00:13:27] Boosters Promo (Disco Dance) M.E. and RLS [00:14:59] Mt. Carmel Lutheran Church PSA - Car Wash (M.E.) [00:15:43] 2nd Annual Auction - Auction held on Nov 14, 1976 to help repay the loan borrowed from ASI. Hosts include Jim Allen and Marv. Auctioned items included $25 of camera work, a mini Hoover washer, and a purse. [00:34:14] The Hardly Worthit Report 12/02/76 1:45-3:00am JAZ, RLS, DH [00:42:01] For Imagination's Sake/Remote - GAZZ9 12/02/76 1:45-3:00am JAZ, RLS, DH [00:47:40] Gallagher and Lyle [00:47:50] Finals Week Madness Hype Off [00:49:30] Rockin' Ronny [00:50:01] David Wayne - Eagles [00:50:31] David Wayne - 3:22am, Hype Contest [00:51:24] KCPR fixing audio transmission equipment, concern with silence and silence [00:55:10] Weisberg Promo - Tim Weisberg, Sunday, Jan 16 in Chumash [00:56:18] Weisberg Interview Promo - Tim Weisberg [00:57:01] Weisberg ID [00:57:08] Edmonds and Curley ID [00:57:27] Dave Mason Promo (DK) - Sunday, Jan 30th [00:58:16] One O'Clock Club Promo (BC) - Friday nights/Saturday early mornings with the Wolf(?) [00:59:14] KCPR vs Womens Volleyball in Basketball (RK, Jaz) - Feb 12th 6pm, Crandall Gym - the Captain, Jim Allen [01:00:31] Tau Beta Pi Cartoon Festival Promo (DK and FT) - Feb 26th 7-9:30pm at Chumash Auditorium [01:01:32] Moon Over Morocco Promo - M-F [01:02:30] Sports Magazine Promo (RB) Randy Baker [01:03:33] Open Channel Promo (DK) - KCPR Public Affairs, Monday March 7 [01:04:06] April Fools Day Promos (MR) [5 promos] [01:07:37] Marshal Trucker Promo (MR) - ASI Concerts [01:09:17] Arm Wrestling Tournament Promo (Donna P, Roy Sasai) - May 17th and 19th [01:10:27] 38 Special Album Giveaway Promo (BC) [01:11:26] Cannon Shot for 38-Special (BC)